Household Food Security, Feeding Practices, and Anthropometric Failure Among Children Aged 6–23 Months: A Hospital-Based Study - Rohan Chatterjee; Soumalya Ray; Dipta Kanti Mukhopadhyay (Indian Journal of Community Medicine)
Background: Household food security (HHFS) and age-appropriate complementary feeding (CF) conceptually play an important role in growth of a child. This study aims to assess the status of HHFS, age-appropriate CF, and undernutrition among children of 6–23 months and their association (if any). Materials and Methods: This institution-based cross-sectional study was conducted among children attending Pediatric OPD of College of Medicine and Sagore Dutta Hospital. Children were assessed regarding age-appropriate complementary feeding using infant and young child feeding (IYCF) practices indicator, nutritional status using composite index of anthropometric failure indicators, and HHFS using standardized and validated HHFS short Bengali version questionnaire. Mothers/primary caregivers were the respondents. Categorical variables were expressed in frequency and percentages. Statistical analysis was done in Jamovi (v2.2.5). Results: 430 mother-child dyads participated in the study with 83.26% of them having low or very low food security. Minimum acceptable diet (MAD) was absent in 74.65% of children and 42.09% of children had single/multiple anthropometric failure(s). Children aged 6–8 months had higher odds of not having MAD (AOR = 3.6, 1.5–8.3). Male gender (AOR = 2.7, 1.7–4.2) and lack of MAD (AOR = 2.7, 1.6–4.7) were associated with anthropometric failure. However, HHFS was not found to be associated with either lack of MAD or anthropometric failure in this study population. Conclusion: Improper transition from exclusive breast feeding to CF may be responsible for higher odds of having lack of MAD in 6–8 months age group, which require strengthening of IEC activity related to IYCF practices on or before initiation of complementary feeding.